Molecular Characterization and Antibacterial Potential of Endophytic Fungal Isolates from Selected Mangroves along the Coastline of Kenya - Teresia Nyambura Wacira; Huxley Mae Makonde; Carren Moraa Bosire; Cromwell Mwiti Kibiti (International Journal of Microbiology)
The increasing emergence and re-emergence of resistant pathogenic microbes causes a health threat to the human population. Scientists have been striving to find novel bioactive compounds and drugs to overcome these obstacles. This study aimed to characterize mangrove endophytic fungi and evaluate their antibacterial activity. Heritiera littoralis, Rhizophora mucronata, Bruguiera gymnorrhiza, Avicennia marina, and Xylocarpus granatum species were collected from Tudor Creek, Mida Creek, and Gazi Bay. A total of 30 fungal isolates were subjected to molecular identification based on analysis of their ITS gene region. The isolates in the inferred phylogenetic trees were affiliated with the genus Aspergillus. Ethyl acetate and butanol crude extracts of 38.2% of the 76 isolated fungal endophytes and eight mycelia samples were screened for antibacterial activity against Staphylococcus aureus (ATCC 27853), Escherichia coli (ATCC 25922), and Pseudomonas aeruginosa (ATCC 25923) using the disc diffusion method. A. marina and R. mucronata harbored the most fungal endophytes that showed the highest antibacterial activity. Seven fungal broth extracts exhibited higher antibacterial activities against the tested microorganisms than the positive control. The minimum inhibitory concentration (MIC) activity for the isolates demonstrated that the ethyl acetate extract of a root endophytic fungal isolate (RC6) (3.31 ± 0.01) of A. marina is a strong inhibitor since it showed significantly lower MIC activity compared to the positive control (3.84 ± 0.00) against Pseudomonas aeruginosa (P<0.05). Therefore, this study confirms that mangrove species harbor fungal isolates that have antibacterial activity and hence could serve as a novel source of antibiotics. It is recommended that the pure compounds from these extracts be isolated for further bioactivity tests and structural elucidation for consideration as lead molecules in drug discovery. In addition, the genes responsible for the enhanced bioactivity in these isolates can be characterized and bioengineered for pharmaceutical application.